2010
DOI: 10.1007/s11663-009-9339-7
|View full text |Cite
|
Sign up to set email alerts
|

On the Dissolution of Nitrided Titanium Defects During Vacuum Arc Remelting of Ti Alloys

Abstract: The elimination of high interstitial defects (also known as hard-a inclusions) is of great importance to the titanium industry. This article presents a model capable of simulating the motion and dissolution of such defects during their residence in the pool of a vacuum arc remelted (VAR) ingot. To predict the complete history of that inclusion, the study couples a dissolution model of the defect and a Lagrangian particle-tracking model. This numerical tool is implemented in SOLAR (solidification during arc rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…This approach is based on a model reported in a previous paper, 8) aimed to simulate the dissolution of hard-α inclusions in molten titanium. This latter model solves, in a one dimensional geometry, the mass transfer equation for nitrogen in a dense inclusion that is in thermal equilibrium with the surrounding liquid.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This approach is based on a model reported in a previous paper, 8) aimed to simulate the dissolution of hard-α inclusions in molten titanium. This latter model solves, in a one dimensional geometry, the mass transfer equation for nitrogen in a dense inclusion that is in thermal equilibrium with the surrounding liquid.…”
Section: Theorymentioning
confidence: 99%
“…They are characterized by their high hardness, which may induce cracks following a fatigue cycle. The dissolution of nitride titanium inclusions has been studied by a number of authors, and both experimental [2][3][4][5][6] and numerical 2,7,8) studies on the subject have been reported. Understanding the inclusion behavior during metal processing has been a major interest at the Institut Jean Lamour (IJL) for many years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach was previously used at Institut Jean Lamour [10,11] to evaluate the impact of process parameters on the dissolution kinetics of high interstitial defects during VAR or electron beam cold hearth refining (EBCHR) of titanium alloys. In addition to the simulation of the thermohydrodynamic behavior of the liquid pool [12] and the particle-tracking model, which will not be discussed in this paper, we have therefore built a comprehensive model of the melting and solidification of a precursor, either in 1D (spherical white spot precursors in a VAR melt pool) or in 2D (cylindrical samples used in the experiments-see below-to validate the numerical simulations).…”
Section: Simulation Of the Melting Of A White Spot Precursormentioning
confidence: 99%
“…The dissolution rate was found to obey a linear correlation with time of 0.16 mm/min under the experimental conditions in his study. Ghazal et al [8] also studied the dissolution rate of TiN in liquid titanium with emphasis on developing a mathematical model. The model was reported to make predictions on the dissolution behavior of the TiN particles as well as their trajectories within the molten pool of a VAR furnace.…”
Section: Introductionmentioning
confidence: 99%